Evolution, knowledge and Christian faith: Gerd Theissen and the credibility of theology - Van Huyssteen, J. Wentzel (Hervormde teologiese studies, 1988)
In this article the way in which Theissen uses the evolutionary paradigm as a comprehensive framework for interpreting not only central themes in theology but also the credibility of theology as such, is analysed from an epistemological point of view. Theissen's overall choice for critical rationalism is critized as an epistemological blurring of paradigms, and thus of models of rationality, and typified as a quest for realism and explanatory progress in theology instead. In interpreting the evolutionary paradigm for theology, Theissen does, however, open up exciting possibilities for retaining the scientific and cognitive status of theological statements.